Investigation of Anatomical Connectivity of Thalamic Stroke Patients using Tract Based Spatial Statistics - (:unkn) unknown (IEEE, 2015)
Diffusion tensor imaging (DTI) techniques allow the detection of changes in the microstructure of the human brain. The detection and follow-up of the underlying pathology and disruption of tissues is of vital importance. Tract-based spatial statistics (TBSS) is a whole brain voxel-by-voxel technique that allows the statistical comparison of the DTI indexes, restricting the analysis to the center of white matter tracts. In the concept of this study, fractional anisotropic differences of the thalamic stroke patients vs control group are investigated and the tracts are reported.
Keywords: DTI; anatomical connectivity; thalamic stroke; TBSS; DIFFUSION TENSOR; TRACTOGRAPHY